Scientific determinants of inclusive entrepreneurship - Zhukovska, Alina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The presented research is devoted to the definition and substantiation of scientific determinants of inclusive entrepreneurship as an innovative tool for overcoming negative trends in socio-economic development and an effective mechanism for solving social problems of society that can not be solved by the state and ignored by entrepreneurs. The aim of the work is a theoretical analysis of the concept of «inclusive entrepreneurship», its distinction with similar concepts, comparative characteristics of the main types of entrepreneurship and charity. To achieve this goal, the following general and special methods were used: induction and deduction, logical generalization, analysis and synthesis, comparison and grouping. The article analyzes the definitions of «social business», «social entrepreneurship», «inclusive business» and «inclusive entrepreneurship» in foreign and domestic literature. The comparative characteristic of the basic principles of functioning of inclusive, commercial and social business and activity of charitable organizations is carried out. The own interpretation of the concept of «inclusive entrepreneurship» is offered. The categories of citizens who can be involved in inclusive entrepreneurship are described in detail. The types of inclusive entrepreneurship are distinguished: youth, women’s, veteran, cross-cultural, «silver», etc. In the conditions of constantly growing social inequality, inclusive entrepreneurship is a promising tool for overcoming any discrimination and realizing the potential of all members of society, regardless of their physical, intellectual, cultural, linguistic, national and other characteristics. The problems of institutionalization of inclusive entrepreneurship, identification of problems and prospects of its development in Ukraine and the world are promising for further scientific research.